Influence of residual solvent on relaxation behavior of polymer films based on glycidyl derivatives of 3, 5, 7, 3',4'-pentahydroxyflavone - Mishurov, D.; Roshal, O.; Brovko, O. (Functional Materials, 2017)
Structural parameters and optical anisotropy relaxation dynamics of cross-linked polymers obtained from 7,4'-diglycidyl-, 7,3',4'-triglycidyl- and 3,7,3',4'-tetraglycidyl ethers of quercetin (3,5,7,3',4'-pentahydroxyflavone) are investigated. Values of effective cross-linked density and molecular weight between the cross-linked units, as well as dynamics of after-poling polymer relaxation were analyzed for polymer films containing residual solvent (acetone) and solvent-free annealed samples. It was found that solvent removal leads to growth of cross-linked density and to decrease of molecular weight between the cross-linked units. It was found that relaxation dynamics of polymers based on 3,7,3',4'-tetraglycidyl quercetin does not depend on the presence of residual solvent. Solvent containing polymers based on 7,4'-diglycidyl- and 7,3',4'-triglycidyl ethers of quercetin have substantially faster relaxation dynamic than corresponding annealed polymers. The mechanism of the residual solvent influence on the relaxation dynamics of polymer films has been proposed.